EFFICACY OF LEVETIRACETAM VERSUS PHENYTOIN AS A SECOND-LINE ANTIEPILEPTIC DRUG IN THE MANAGEMENT OF BENZODIAZEPINE-REFRACTORY STATUS EPILEPTICUS AMONG CHILDREN - Naeem, Babar; Ashfaq , Mommna; Qureshi, Mamoon Akbar (Journal of Ayub Medical College Abbottabad, 2023)
Background: Status Epilepticus (SE) is a life-threatening neurological emergency requiring appropriate therapy to terminate seizure activity. SE is managed with supportive measures and ultra-short-acting benzodiazepines. However, limited data is available in the paediatric population regarding the next best option when this fails. This study aimed at finding new data to recommend levetiracetam or phenytoin as the second-line option. Methods: One hundred and thirty-seven patients with status epilepticus were randomized into two groups; group-I was given IV Levetiracetam (LEV) at 20 mg/kg/dose over 5 minutes followed by a maintenance dose of 20mg/kg/dose BID, whereas Group II received phenytoin at 20mg/kg IV loading dose followed by a maintenance dose of 5-8 mg/kg/day divided BID. The primary outcome was seizure cessation, defined as the termination of the apparent convulsion 30'‰min after the administration of phenytoin or levetiracetam. Secondary outcomes were the use of different anti-convulsants for continued management, admittance to critical treatment, and severe adverse events (including mortality, Stevens-Johnson syndrome, rash, airway problems, cardiovascular instability, extravasation, and severe agitation). Data was recorded via a clinical proforma and was analyzed by SPSS software version 25. All numerical data were expressed in mean±SD forms, and frequency was determined for qualitative baseline data. Secondary outcomes were tested through the Ï‡2 test, A p-value of ‰¤0.05 was considered statistical significance. Results: Levetiracetam terminated seizures in 94% of children compared to 77% in those treated with phenytoin. The mean time to seizure termination was 19.94±3.76 minutes for the LEV Group as compared to 23.791±9.1 min for the PHT group. (p=0.046). Regarding safety, a profile study shows LEV has fewer and less severe side effects compared to Phenytoin. Conclusion: Levetiracetam is a safe, well-tolerated, and effective treatment as a second-line antiepileptic drug in the management of status epilepticus.